EFEKTIVITAS MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR PESERTA DIDIK - Nadiah; Siti Hanafiah (Fakultas Agama Islam Universitas Islam Jakarta, 2022)
This research is motivated because learning is a complex process that occurs in everyone. A learning model implemented in the classroom will affect the learning process in schools that aim to direct changes in student. With the learning model makes it easier for students to catch a lesson. Student leaning outcomes are also an important and driving factor to determine the learning achievement so far in the classroom. Because with the right learning model, students will be encouraged to learn and will produce maximum grades. The results of the study are in the terms of the global test coefficient test. The result in the F test or global test is the F test result number of 20,851 and if viewed from the Fcount of 20,851, it is greater than Ftable 4,38 with a significant level of 0,00. This means that the Mind Mapping learning model has a very strong effectiviness on the ongoing learning process.